The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.5195/jmla.2018.354
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of health information professionals for library and information science curriculum development: a scoping review

Abstract: ObjectiveThis scoping review identified the emerging and evolving roles of health information professionals (HIPs) in a range of tasks and settings, as they adapt to varied user needs, while keeping up with changing medical landscapes to provide evidence-based information support in grand rounds and scholarly research. The review aims to inform library school students about expected entry-level job qualifications and faculty about adaptable changes to specialized HIP curricula.MethodsThe authors examined 268 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 65 publications
(92 reference statements)
0
40
1
Order By: Relevance
“…Clinical librarians are often part of the patient clinical care team, as experts in health care information/data, and part of the research teams because they are regularly required to participate in medical procedures by conducting research, attending and participating in medical seminars and providing specialised information to the interested parties (Ma, Stahl, & Knotts, 2018). One of their main contributions to the health world is the connection between the medical literature and the patient care (Ma et al, 2018). In this article, our main attempt is to follow this line and report new information technology systems retrieved from present literature in order to provide health librarians with specialist knowledge about health information resources.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical librarians are often part of the patient clinical care team, as experts in health care information/data, and part of the research teams because they are regularly required to participate in medical procedures by conducting research, attending and participating in medical seminars and providing specialised information to the interested parties (Ma, Stahl, & Knotts, 2018). One of their main contributions to the health world is the connection between the medical literature and the patient care (Ma et al, 2018). In this article, our main attempt is to follow this line and report new information technology systems retrieved from present literature in order to provide health librarians with specialist knowledge about health information resources.…”
Section: Discussionmentioning
confidence: 99%
“…A strong body of literature has appeared in the past decade on predicted changes in the health librarian profession. The scoping review by Ma, Stahl, and Knotts (2018) described nine evolving and active roles, with embedded librarians as a strong theme. Several authors have identified external and occupational drivers of change, and discussed the need for the profession to respond (Brettle & Urquhart, 2011;Crum & Cooper, 2013;Henderson, 2014;Holst et al, 2009;Hopkins, 2017;King & Lapidus, 2015;McGowan, 2012;Murphy, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Group 9 also confirmed that they were aspiring to see "the clarity of the provisions of the Guide on the functions of the information professional, and not as a specialist of the learning resource and the direct responsibility for it.The information professionals have to know clearly the functions of information professionals". However, Ma and Stahl (2018) stated that students obtain better information literacy instruction through their problem-based classroom learning when instructors allow librarians full access to the courses and present librarians to the students to integrate them into the learning environment. This situation leads to instruction has become more about teaching selfsufficiency than serving as a gatekeeper of information.…”
Section: The Learning Resource Specialists View Regarding Their Careermentioning
confidence: 99%
“…The findings show that health sciences librarians are often expected to attend curriculum committee meetings and reach out to students both within and outside the classroom. They emphasized that librarians can play critical roles in developing course competencies and sharing them with other instructors (Ma and Stahl, 2018).…”
Section: The Learning Resource Specialists View Regarding Their Careermentioning
confidence: 99%
See 1 more Smart Citation